Soft magnetic composite material and preparation method thereof

By covering the alloy powder surface of the soft magnetic composite material with phosphating layer, silicon oxide layer and sodium silicate layer, the problem of high eddy current loss at high frequency is solved, and the effect of reducing eddy current loss and improving the performance of power devices is achieved.

CN119724805APending Publication Date: 2025-03-28SHENZHEN SUNLORD ELECTRONICS
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411901934.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing soft magnetic composite materials are limited by their application range due to high eddy current losses, large power consumption and severe heat generation at high frequencies.

Method used

By sequentially coating the alloy powder surface in the soft magnetic composite material with a phosphating layer, a silicon oxide layer and a sodium silicate layer, mutual insulation between the powder particles is achieved, thereby reducing eddy current loss at high frequency.

Benefits of technology

It effectively reduces the eddy current loss between particles at high frequencies, improves the overall performance of power devices, and is conducive to large-scale promotion and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724805A_ABST
    Figure CN119724805A_ABST
Patent Text Reader

Abstract

The invention provides a soft magnetic composite material and a preparation method thereof. The soft magnetic composite material is composed of amorphous nanocrystalline coated powder and iron-based alloy coated powder. Wherein the amorphous nanocrystalline coated powder comprises an amorphous nanocrystalline core and a first insulating coating layer group, and the iron-based alloy coated powder comprises an iron-based core and a second insulating coating layer group; the first insulating coating layer group and the second insulating coating layer group respectively and independently comprise a phosphate coating, a silicon oxide layer and a sodium silicate layer which are stacked, and the phosphate coating is arranged on the surface of the inner core. The surface of the alloy powder in the soft magnetic composite material is sequentially coated with the phosphate coating, the silicon oxide layer and the sodium silicate layer, mutual insulation between powder particles is achieved, eddy current generated between the particles under high frequency is effectively reduced, then eddy current loss is reduced, the overall performance of a power device is improved, and large-scale application and popularization are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic materials and relates to a soft magnetic composite material, in particular to a soft magnetic composite material and a preparation method thereof. Background Art

[0002] Soft magnetic materials and related devices, including transformers, inductors, chokes and filters, play a vital role in energy storage, conversion and transmission, and have a profound impact on people's daily lives. In recent years, with the rapid development of new energy vehicles, 5G technology, data processing and storage, and AI technology, the market has put forward greater challenges to the performance of electronic components. In addition, with the further development of power devices towards high power density and high conversion efficiency, related technical fields have put forward higher requirements on the power consumption and heat dissipation performance of each device.

[0003] Soft magnetic composite materials are usually composed of metal powder coated with an electrical insulation layer. They have rich distribution atmosphere and interface, low eddy current loss, magnetic isotropy and flexible structural design, which makes them stand out among soft magnetic materials for high-frequency applications. Metal soft magnetic materials are widely used due to their excellent performance. However, due to the low resistivity and skin effect of metal materials, the eddy current is large at high frequencies, the power consumption is high, and the heat is serious, which deteriorates the performance and limits the application of metal soft magnetic materials.

[0004] CN117612818A discloses a nanocrystalline mixed magnetic powder core for molded inductors and a preparation method thereof, the core of which is to introduce soft magnetic materials of different particle sizes to realize the preparation of nanocrystalline mixed magnetic powder core for molded inductors with high saturation magnetization intensity, high DC bias and low loss under low voltage conditions. A uniformly distributed SiO2 insulating layer is formed on the surface of the nanocrystalline magnetic powder by a sol-gel method, and at the same time, the ultrafine high Bs powder is passivated and coated with phosphoric acid to improve the material resistivity, reduce the eddy current loss of the magnetic powder core and improve the DC bias characteristics of the magnetic powder core. In addition, the size of the ultrafine high Bs powder can also reduce the eddy current loss of the magnetic powder core, making the nanocrystalline mixed magnetic powder core prepared by the invention one of the preferred soft magnetic materials for molded inductors, meeting the development trend of high frequency and energy saving. However, due to the power consumption limitation of the 1K-107 nanocrystalline and the homemade FeSiBCuNbP(C) nanocrystalline sold on the market, the volume power consumption of the final nanocrystalline mixed magnetic powder core still needs to be further reduced.

[0005] It can be seen that how to provide a soft magnetic composite material and a preparation method thereof to reduce inter-particle eddy current loss and thereby improve the overall performance of power devices has become an urgent problem that technical personnel in this field need to solve. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a soft magnetic composite material and a preparation method thereof. By sequentially coating the surface of the alloy powder in the soft magnetic composite material with a phosphide layer, a silicon oxide layer and a sodium silicate layer, mutual insulation between the powder particles is achieved, the eddy current generated between the particles at high frequencies is effectively reduced, and the eddy current loss is thereby reduced, thereby improving the overall performance of the power device and facilitating large-scale promotion and application.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a soft magnetic composite material, wherein the soft magnetic composite material is composed of amorphous nanocrystalline coated powder and iron-based alloy coated powder.

[0009] The amorphous nanocrystalline coated powder comprises an amorphous nanocrystalline core and a first insulating coating layer group, and the iron-based alloy coated powder comprises an iron-based core and a second insulating coating layer group.

[0010] The first insulating coating layer group includes a first phosphide layer, a first silicon oxide layer and a first sodium silicate layer which are stacked, and the first phosphide layer is arranged on the surface of the amorphous nanocrystalline core.

[0011] The second insulating coating layer group includes a second phosphide layer, a second silicon oxide layer and a second sodium silicate layer which are stacked, and the second phosphide layer is arranged on the surface of the iron-based core.

[0012] In the present invention, the chemical formula of the amorphous nanocrystalline core is: Fe (100-a-b-c-d-e-f-g) Co a Si b B c Cu d Nb e P f V g .

[0013] Among them, 5≤a≤12, 3≤b≤12, 4≤c≤10, 0.5≤d≤1.6, 2.0≤e≤3.7, 3≤f≤6, 0.3≤g≤2.0, and 18≤(b+c+f)≤26.

[0014] In the present invention, in the amorphous nanocrystalline core, the average grain size of the nanocrystalline is 10-20 nm, and the crystallinity is ≥50%.

[0015] And / or, the D50 particle size of the amorphous nanocrystalline core is 10-30 μm.

[0016] And / or, the material of the iron-based core includes any one of carbonyl iron, reduced iron, iron silicon or iron silicon chromium, or a combination of at least two thereof.

[0017] And / or, the D50 particle size of the iron-based inner core is 4-10 μm.

[0018] In the present invention, the average thickness of the first phosphating layer is 5-70 nm.

[0019] And / or, the average thickness of the first silicon oxide layer is 10-100 nm.

[0020] And / or, the average thickness of the first sodium silicate layer is 10-100 nm.

[0021] In the present invention, the average thickness of the second phosphating layer is 5-70 nm.

[0022] And / or, the average thickness of the second silicon oxide layer is 10-100 nm.

[0023] And / or, the average thickness of the second sodium silicate layer is 10-100 nm.

[0024] In a second aspect, the present invention provides a method for preparing the soft magnetic composite material as described in the first aspect, the preparation method comprising the following steps:

[0025] (1) Amorphous alloy powder is prepared by a water vapor combined atomization method, and amorphous nanocrystalline powder is obtained after rapid heat treatment;

[0026] (2) subjecting the amorphous nanocrystalline powder and the iron-based alloy powder to phosphating treatment, silica sol coating treatment and sodium silicate coating treatment respectively, to obtain amorphous nanocrystalline coated powder and iron-based alloy coated powder respectively;

[0027] (3) mixing amorphous nanocrystalline coated powder and iron-based alloy coated powder to obtain graded powder;

[0028] (4) The graded powder is sequentially granulated, pressed and heat treated to obtain a soft magnetic composite material.

[0029] In the present invention, the heating rate of the rapid heat treatment in step (1) is 200-250°C / min, and the target temperature is 450-600°C.

[0030] In the present invention, the phosphating treatment in step (2) comprises: mixing the alloy powder and the phosphating solution, stirring them evenly under heating conditions, and drying them to obtain a first powder.

[0031] Wherein, the alloy powder includes amorphous nanocrystalline powder and / or iron-based alloy powder.

[0032] And / or, the solute of the phosphating solution includes phosphoric acid, zinc dihydrogen phosphate and nickel nitrate.

[0033] And / or, the mixing mass ratio of the solute in the phosphating solution to the alloy powder is (0.05-1):100.

[0034] And / or, the solvent of the phosphating solution includes any one of deionized water, anhydrous ethanol or acetone, or a combination of at least two of them.

[0035] And / or, the mixing mass ratio of the solvent of the phosphating solution to the alloy powder is (6-20):100.

[0036] In the present invention, the silica sol coating treatment in step (2) comprises: mixing the first powder and the silica sol, stirring them evenly under heating conditions, and drying them to obtain the second powder.

[0037] The silica sol is a dispersion of silica particles in deionized water, and the mass ratio of the silica particles to the deionized water is (2.5-30):100.

[0038] And / or, the mixing mass ratio of the silicon dioxide particles to the first powder in the silica sol is (0.5-3):100.

[0039] In the present invention, the sodium silicate coating treatment in step (2) comprises: mixing the second powder and the sodium silicate solution, stirring evenly under heating conditions, and drying to obtain amorphous nanocrystalline coated powder and / or iron-based alloy coated powder.

[0040] Wherein, the sodium silicate solution is a mixed solution of sodium silicate nonahydrate and deionized water, and the mass ratio of the sodium silicate nonahydrate to the deionized water is (2.5-20):100.

[0041] And / or, the mixing mass ratio of sodium silicate nonahydrate to the second powder in the sodium silicate solution is (0.5-2):100.

[0042] In the present invention, the mixing mass ratio of the amorphous nanocrystalline coated powder and the iron-based alloy coated powder in step (3) is (25-100):100.

[0043] And / or, the granulation in step (4) includes: mixing the graded powder and the epoxy resin solution, and drying to obtain granulated powder.

[0044] The solvent of the epoxy resin solution includes any one of acetone, ethanol, toluene or xylene, or a combination of at least two of them.

[0045] And / or, the heat treatment in step (4) is carried out in air, nitrogen or argon.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] (1) The present invention achieves mutual insulation between powder particles by sequentially coating the surface of alloy powder in the soft magnetic composite material with a high resistivity phosphide layer, a silicon oxide layer and a sodium silicate layer, effectively reducing the eddy current generated between particles at high frequencies, thereby reducing eddy current losses, improving the overall performance of power devices, and facilitating large-scale promotion and application.

[0048] (2) The present invention performs rapid heat treatment on amorphous alloy powder so that the atoms or molecules in the material obtain sufficient energy to rearrange the structure in a short time. Since the growth process of the grains is significantly suppressed and more crystal nuclei are formed inside the material, the final grain size is nanometer scale, that is, nanocrystals are precipitated to obtain amorphous nanocrystalline powder, which further reduces the coercive force and power consumption of the soft magnetic composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 is the X-ray diffraction pattern of the amorphous nanocrystalline powder provided in Example 1;

[0050] Figure 2 It is a comparison chart of the soft magnetic composite materials obtained in Example 1 and Comparative Example 7 after 24h salt spray resistance test. DETAILED DESCRIPTION

[0051] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0052] A certain embodiment of the present invention provides a soft magnetic composite material, wherein the soft magnetic composite material is composed of amorphous nanocrystalline coated powder and iron-based alloy coated powder.

[0053] The amorphous nanocrystalline coated powder comprises an amorphous nanocrystalline core and a first insulating coating layer group, and the iron-based alloy coated powder comprises an iron-based core and a second insulating coating layer group.

[0054] The first insulating coating layer group includes a first phosphide layer, a first silicon oxide layer and a first sodium silicate layer which are stacked, and the first phosphide layer is arranged on the surface of the amorphous nanocrystalline core.

[0055] The second insulating coating layer group includes a second phosphide layer, a second silicon oxide layer and a second sodium silicate layer which are stacked, and the second phosphide layer is arranged on the surface of the iron-based core.

[0056] The present invention achieves mutual insulation between powder particles by sequentially coating the surface of alloy powder in the soft magnetic composite material with a high resistivity phosphide layer, a silicon oxide layer and a sodium silicate layer, effectively reducing eddy currents generated between particles at high frequencies, thereby reducing eddy current losses, improving the overall performance of power devices, and facilitating large-scale promotion and application.

[0057] In some embodiments, the chemical formula of the amorphous nanocrystal core is: Fe (100-a-b-c-d-e-f-g) Co a Si b B c Cu d Nb e P f V g .

[0058] Among them, 5≤a≤12, for example, a=5, 6, 7, 8, 9, 10, 11 or 12; 3≤b≤12, for example, b=3, 4, 5, 6, 7, 8, 9, 10, 11 or 12; 4≤c≤10, for example, c=4, 5, 6, 7, 8, 9 or 10; 0.5≤d≤1.6, for example, d=0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5 or 1.6; 2.0≤e≤3.7, for example, e=2.0, 2.2, 2.4, 2.6 , 2.8, 3.0, 3.2, 3.4, 3.6 or 3.7; 3≤f≤6, for example, f=3, 3.5, 4, 4.5, 5, 5.5 or 6; 0.3≤g≤2.0, for example, g=0.3, 0.4, 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8 or 2.0, and 18≤(b+c+f)≤26, for example, b+c+f=18, 19, 20, 21, 22, 23, 24, 25 or 26, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0059] In the present invention, the addition of Co element helps to adjust the saturation magnetostriction coefficient λs of the material, thereby achieving low power consumption characteristics; the addition of V element increases the negative enthalpy between V and B (-42 kJ / mol), inhibits the precipitation of Fe-B compounds, and at the same time, the appropriate V content increases the temperature difference ΔTx between the precipitation of α-Fe(Si) and Fe-B phases, thereby increasing the heat treatment temperature range during crystallization; the solubility of P element in α-Fe grains is negligible, and it segregates in the residual amorphous matrix, making the dispersion of α-Fe(Si) grains in the matrix finer and more uniform.

[0060] In addition, the atomic radius of V (0.135nm) and Nb (0.148nm) is relatively large, while the atomic radius of Fe (0.127nm) and B (0.095nm) is relatively small. The obvious difference between the atomic radii of multi-component materials will form a tighter disordered stacking, thereby increasing the melt viscosity and density, reducing the crystallization kinetics during cooling, and ultimately improving the amorphous forming ability.

[0061] In some embodiments, the average grain size of the nanocrystals is 10-20nm, for example, it can be 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm or 20nm, and the crystallinity is ≥50%, for example, it can be 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68% or 70%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0062] In some embodiments, the D50 particle size of the amorphous nanocrystal core is 10-30μm, for example, it can be 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 22μm, 24μm, 26μm, 28μm or 30μm, and is more preferably 15-20μm, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0063] In some embodiments, the material of the iron-based core includes any one of carbonyl iron, reduced iron, iron silicon or iron silicon chromium, or a combination of at least two of them. Typical but non-limiting combinations include a combination of carbonyl iron and reduced iron, a combination of reduced iron and iron silicon, or a combination of iron silicon and iron silicon chromium.

[0064] In some embodiments, the D50 particle size of the iron-based core is 4-10μm, for example, it can be 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm or 10μm, and is more preferably 5-8μm, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0065] In some embodiments, the average thickness of the first phosphating layer is 5-70nm, for example, it can be 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm or 70nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0066] In some embodiments, the average thickness of the first silicon oxide layer is 10-100 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] In some embodiments, the average thickness of the first sodium silicate layer is 10-100 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] In some embodiments, the average thickness of the second phosphide layer is 5-70nm, for example, it can be 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm or 70nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0069] In some embodiments, the average thickness of the second silicon oxide layer is 10-100 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0070] In some embodiments, the average thickness of the second sodium silicate layer is 10-100 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] A certain embodiment of the present invention provides a method for preparing the above-mentioned soft magnetic composite material, the preparation method comprising the following steps:

[0072] (1) Amorphous alloy powder is prepared by a water vapor combined atomization method, and amorphous nanocrystalline powder is obtained after rapid heat treatment;

[0073] (2) subjecting the amorphous nanocrystalline powder and the iron-based alloy powder to phosphating treatment, silica sol coating treatment and sodium silicate coating treatment respectively, to obtain amorphous nanocrystalline coated powder and iron-based alloy coated powder respectively;

[0074] (3) mixing amorphous nanocrystalline coated powder and iron-based alloy coated powder to obtain graded powder;

[0075] (4) The graded powder is sequentially granulated, pressed and heat treated to obtain a soft magnetic composite material.

[0076] In the present invention, the water vapor combined atomization method described in step (1) is a common method in the industry, which breaks the molten metal flow into powder by the combined action of high-pressure water flow and inert gas (such as nitrogen). As long as the preparation of amorphous alloy powder can be achieved, the specific preparation conditions of the water vapor combined atomization method are not particularly limited here.

[0077] The present invention performs rapid heat treatment on amorphous alloy powder so that atoms or molecules in the material obtain sufficient energy in a short time to rearrange the structure. Since the growth process of the grains is significantly suppressed and more crystal nuclei are formed inside the material, the grain size finally formed is nanometer scale, that is, nanocrystals are precipitated to obtain amorphous nanocrystalline powder, which further reduces the coercive force and power consumption of the soft magnetic composite material.

[0078] In some embodiments, the heating rate of the rapid heat treatment in step (1) is 200-250°C / min, for example, 200°C / min, 205°C / min, 210°C / min, 215°C / min, 220°C / min, 225°C / min, 230°C / min, 235°C / min, 240°C / min, 245°C / min or 250°C / min, and the target temperature is 450-600°C, for example, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C ℃, 470℃, 480℃, 490℃, 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, 560℃, 570℃, 580℃, 590℃ or 600℃, and the holding time is ≤10min, for example, it can be 1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min or 10min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0079] The present invention achieves time-saving and energy-saving production requirements while preparing amorphous nanocrystalline powder by specifically limiting the specific parameters of rapid thermal treatment, and has lower carbon emissions.

[0080] The present invention specifically limits the target temperature of rapid thermal treatment to 450-600°C, and the specific temperature value can be adaptively adjusted according to the composition of the amorphous alloy powder. If the temperature is too low, nanocrystals cannot be formed; if the temperature is too high, borides will precipitate and the material properties will deteriorate.

[0081] In some embodiments, the phosphating treatment in step (2) includes: mixing the alloy powder and the phosphating solution, stirring them evenly under heating conditions, and drying them to obtain a first powder.

[0082] Wherein, the alloy powder includes amorphous nanocrystalline powder and / or iron-based alloy powder.

[0083] In the present invention, the heating temperature is ≤120°C, for example, it can be 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, and the stirring rate is 100-200rpm, for example, it can be 100rpm, 110rpm, 120rpm, 130rpm, 140rpm, 150rpm, 160rpm, 170rpm, 180rpm, 190rpm or 200rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0084] In certain embodiments, the solute of the phosphating solution includes phosphoric acid, zinc dihydrogen phosphate and nickel nitrate.

[0085] In some embodiments, the mixing mass ratio of the solute in the phosphating solution to the alloy powder is (0.05-1):100, for example, it can be 0.05:100, 0.1:100, 0.2:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, 0.9:100 or 1:100, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0086] In some embodiments, the solvent of the phosphating solution includes any one of deionized water, anhydrous ethanol or acetone, or a combination of at least two of them. Typical but non-limiting combinations include a combination of deionized water and anhydrous ethanol, a combination of anhydrous ethanol and acetone, a combination of deionized water and acetone, or a combination of deionized water, anhydrous ethanol and acetone.

[0087] In some embodiments, the mixing mass ratio of the solvent of the phosphating solution to the alloy powder is (6-20):100, for example, it can be 6:100, 8:100, 10:100, 12:100, 14:100, 16:100, 18:100 or 20:100, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0088] In certain embodiments, the silica sol coating treatment in step (2) includes: mixing the first powder and the silica sol, stirring them uniformly under heating conditions, and drying to obtain the second powder.

[0089] The silica sol is a dispersion of silica particles in deionized water, and the mass ratio of the silica particles to deionized water is (2.5-30):100, for example, 2.5:100, 5:100, 10:100, 15:100, 20:100, 25:100 or 30:100, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0090] In the present invention, the heating temperature is ≤200°C, for example, it can be 20°C, 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C or 200°C, and the stirring rate is 100-200rpm, for example, it can be 100rpm, 110rpm, 120rpm, 130rpm, 140rpm, 150rpm, 160rpm, 170rpm, 180rpm, 190rpm or 200rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0091] In some embodiments, the mixing mass ratio of the silica particles to the first powder in the silica sol is (0.5-3):100, for example, it can be 0.5:100, 1:100, 1.5:100, 2:100, 2.5:100 or 3:100, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0092] In certain embodiments, the sodium silicate coating treatment in step (2) includes: mixing the second powder and the sodium silicate solution, stirring evenly under heating conditions, and drying to obtain an amorphous nanocrystalline coated powder and / or an iron-based alloy coated powder.

[0093] The sodium silicate solution is a mixed solution of sodium silicate nonahydrate and deionized water, and the mass ratio of the sodium silicate nonahydrate to the deionized water is (2.5-20):100, for example, it can be 2.5:100, 4:100, 6:100, 8:100, 10:100, 12:100, 14:100, 16:100, 18:100 or 20:100, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0094] In the present invention, the heating temperature is ≤200°C, for example, it can be 20°C, 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C or 200°C, and the stirring rate is 100-200rpm, for example, it can be 100rpm, 110rpm, 120rpm, 130rpm, 140rpm, 150rpm, 160rpm, 170rpm, 180rpm, 190rpm or 200rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0095] In certain embodiments, the mixing mass ratio of sodium silicate nonahydrate to the second powder in the sodium silicate solution is (0.5-2):100, for example, it can be 0.5:100, 0.6:100, 0.8:100, 1:100, 1.2:100, 1.4:100, 1.6:100, 1.8:100 or 2:100, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0096] In some embodiments, the mixing mass ratio of the amorphous nanocrystalline coated powder and the iron-based alloy coated powder in step (3) is (25-100):100, for example, it can be 25:100, 30:100, 35:100, 40:100, 45:100, 50:100, 55:100, 60:100, 65:100, 70:100, 75:100, 80:100, 85:100, 90:100, 95:100 or 100:100, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0097] In certain embodiments, the granulation in step (4) comprises: mixing the graded powder and the epoxy resin solution, and drying to obtain granulated powder.

[0098] The solvent of the epoxy resin solution includes any one of acetone, ethanol, toluene or xylene, or a combination of at least two of them. Typical but non-limiting combinations include a combination of acetone and ethanol, a combination of ethanol and toluene, a combination of toluene and xylene, a combination of acetone, ethanol and toluene, a combination of ethanol, toluene and xylene, or a combination of acetone, ethanol, toluene and xylene.

[0099] In the present invention, the mixing mass ratio of the solvent to the graded powder in the epoxy resin solution is (6-30):100, for example, it can be 6:100, 8:100, 10:100, 12:100, 14:100, 16:100, 18:100, 20:100, 22:100, 24:100, 26:100, 28:100 or 30:100, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0100] In the present invention, the mixing mass ratio of the solute to the graded powder in the epoxy resin solution is (0.5-3):100, for example, it can be 0.5:100, 0.75:100, 1:100, 1.25:100, 1.5:100, 1.75:100, 2:100, 2.25:100, 2.5:100, 2.75:100 or 3:100, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0101] In certain embodiments, the heat treatment in step (4) is carried out in air, nitrogen or argon, and the insulation temperature is 50-300°C, for example, it can be 50°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 240°C, 260°C, 280°C or 300°C, and the insulation time is ≤24h, for example, it can be 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0102] However, it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0103] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0104] Example 1

[0105] This embodiment provides a soft magnetic composite material and a preparation method thereof, the preparation method comprising the following steps:

[0106] (1) Amorphous alloy powder is prepared by water vapor combined atomization method, and its chemical formula is: Fe 62 Co 10 Si 12 B6 1.2 Nb 2.8 P5V1, after sieving, a powder with a D50 particle size of 18 μm was obtained; the temperature was raised to 500°C at a rate of 230°C / min and kept at this temperature for 5 min to obtain amorphous nanocrystalline powder.

[0107] (2) performing insulation coating treatment on the amorphous nanocrystalline powder, specifically comprising:

[0108] (2.1) Weigh 0.05 parts of phosphoric acid, 0.025 parts of zinc dihydrogen phosphate and 0.025 parts of nickel nitrate, dissolve them in 15 parts of deionized water to obtain a phosphating solution A; weigh 100 parts of amorphous nanocrystalline powder, add them to the phosphating solution A, stir them evenly at 80° C., control the stirring speed to 120 rpm, until the powder is completely dry, to obtain a first powder A;

[0109] (2.2) Adding silica sol A prepared by mixing 0.5 parts of silica particles and 15 parts of deionized water to 100 parts of the first powder A, stirring the mixture at 120° C. and controlling the stirring speed to 120 rpm until the powder is completely dry, thereby obtaining a second powder A;

[0110] (2.3) Add sodium silicate solution A prepared by mixing 0.5 parts of sodium silicate nonahydrate and 10 parts of deionized water to 100 parts of the second powder A, stir evenly at 120° C., and control the stirring speed to 120 rpm until the powder is completely dry. After sieving, an amorphous nanocrystalline coated powder with an average particle size of 60 mesh is obtained.

[0111] (3) Insulating and coating the carbonyl iron powder, specifically comprising:

[0112] (3.1) Weigh 0.1 parts of phosphoric acid, 0.025 parts of zinc dihydrogen phosphate and 0.025 parts of nickel nitrate, and dissolve them in 15 parts of deionized water to obtain a phosphating solution B; weigh 100 parts of carbonyl iron powder with a D50 particle size of 7 μm, add it to the phosphating solution B, stir evenly at 80° C., control the stirring speed to 120 rpm, until the powder is completely dry, to obtain a first powder B;

[0113] (3.2) Adding silica sol B prepared by mixing 0.8 parts of silica particles and 15 parts of deionized water to 100 parts of the first powder B, stirring the mixture at 120° C. and controlling the stirring speed to 120 rpm until the powder is completely dry, thereby obtaining a second powder B;

[0114] (3.3) Add sodium silicate solution B prepared by mixing 1 part of sodium silicate nonahydrate and 10 parts of deionized water to 100 parts of the second powder B, stir evenly at 120° C. and control the stirring speed to 120 rpm until the powder is completely dry. After sieving, an iron-based alloy coated powder with an average particle size of 60 mesh is obtained.

[0115] (4) Weigh 25 parts of amorphous nanocrystalline coated powder and 75 parts of iron-based alloy coated powder, mix them evenly to obtain graded powder.

[0116] (5) Weigh 1.5 parts of epoxy resin and 20 parts of acetone, mix well, add graded powder, stir thoroughly and air-dry, and sieve to obtain granulated powder with an average particle size of 200 mesh.

[0117] (6) The granulated powder is directly pressed into a magnetic ring and then pressed into a green body with copper wire.

[0118] (7) The green body is heat treated at 200°C in air and kept warm for 1 hour to obtain a soft magnetic composite material.

[0119] It can be seen from the above preparation method that the soft magnetic composite material provided in this embodiment is composed of amorphous nanocrystalline coated powder and iron-based alloy coated powder. Among them, the amorphous nanocrystalline coated powder includes an amorphous nanocrystalline core and a first insulating coating layer group, and the iron-based alloy coated powder includes a carbonyl iron core and a second insulating coating layer group; the first insulating coating layer group includes a first phosphating layer, a first silicon oxide layer and a first sodium silicate layer stacked, and the first phosphating layer is arranged on the surface of the amorphous nanocrystalline core; the second insulating coating layer group includes a second phosphating layer, a second silicon oxide layer and a second sodium silicate layer stacked, and the second phosphating layer is arranged on the surface of the iron-based core.

[0120] Figure 1 This is the X-ray diffraction spectrum of the amorphous nanocrystalline powder obtained in this example. By calculating the area ratio of the diffraction peaks of the crystalline phase and the amorphous phase, it can be obtained that the crystallinity of the amorphous nanocrystalline powder is 83%.

[0121] In addition, by analyzing the X-ray diffraction spectrum, it can be known that in the amorphous nanocrystalline powder obtained in this embodiment, the average grain size of the nanocrystalline is 13.4 nm.

[0122] After testing, in the amorphous nanocrystalline coated powder obtained in this embodiment, the average thickness of the first phosphide layer is 11nm, the average thickness of the first silicon oxide layer is 13nm, and the average thickness of the first sodium silicate layer is 15nm; in the iron-based alloy coated powder obtained in this embodiment, the average thickness of the second phosphide layer is 14nm, the average thickness of the second silicon oxide layer is 20nm, and the average thickness of the second sodium silicate layer is 41nm.

[0123] Example 2

[0124] This embodiment provides a soft magnetic composite material and a preparation method thereof, the preparation method comprising the following steps:

[0125] (1) Amorphous alloy powder is prepared by water vapor combined atomization method, and its chemical formula is: Fe 67 Co6Si 10 B 10 Cu1Nb 2.5 P3V 0.5 , after sieving, a powder with a D50 particle size of 10 μm was obtained; the temperature was raised to 530°C at a rate of 200°C / min and kept warm for 10 minutes to obtain amorphous nanocrystalline powder.

[0126] (2) performing insulation coating treatment on the amorphous nanocrystalline powder, specifically comprising:

[0127] (2.1) Weigh 0.03 parts of phosphoric acid, 0.015 parts of zinc dihydrogen phosphate and 0.015 parts of nickel nitrate, dissolve them in 20 parts of anhydrous ethanol to obtain a phosphating solution A; weigh 100 parts of amorphous nanocrystalline powder, add them to the phosphating solution A, stir them evenly at 80° C., control the stirring speed to 120 rpm, until the powder is completely dry, to obtain a first powder A;

[0128] (2.2) Adding silica sol A prepared by mixing 0.5 parts of silica particles and 50 parts of deionized water to 100 parts of the first powder A, stirring the mixture at 120° C. and controlling the stirring speed to 120 rpm until the powder is completely dry, thereby obtaining a second powder A;

[0129] (2.3) Add sodium silicate solution A prepared by mixing 2 parts of sodium silicate nonahydrate and 20 parts of deionized water to 100 parts of the second powder A, stir evenly at 120° C. and control the stirring speed to 120 rpm until the powder is completely dry. After sieving, an amorphous nanocrystalline coated powder with an average particle size of 60 mesh is obtained.

[0130] (3) Insulating and coating the iron silicon powder, specifically comprising:

[0131] (3.1) Weigh 0.3 parts of phosphoric acid, 0.15 parts of zinc dihydrogen phosphate and 0.15 parts of nickel nitrate, dissolve them in 20 parts of anhydrous ethanol to obtain a phosphating solution B; weigh 100 parts of iron silicon powder with a D50 particle size of 10 μm, add it to the phosphating solution B, stir evenly at 80° C., control the stirring speed to 120 rpm, until the powder is completely dry, and obtain a first powder B;

[0132] (3.2) Adding silica sol B prepared by mixing 0.5 parts of silica particles and 50 parts of deionized water to 100 parts of the first powder B, stirring the mixture at 120° C. and controlling the stirring speed to 120 rpm until the powder is completely dry, thereby obtaining a second powder B;

[0133] (3.3) Add sodium silicate solution B prepared by mixing 1 part of sodium silicate nonahydrate and 20 parts of deionized water to 100 parts of the second powder B, stir evenly at 120° C. and control the stirring speed to 120 rpm until the powder is completely dry. After sieving, an iron-based alloy coated powder with an average particle size of 60 mesh is obtained.

[0134] (4) Weigh 40 parts of amorphous nanocrystalline coated powder and 60 parts of iron-based alloy coated powder, mix them evenly to obtain graded powder.

[0135] (5) Weigh 1.5 parts of epoxy resin and 20 parts of toluene, mix well, add graded powder, stir thoroughly and air-dry, and sieve to obtain granulated powder with an average particle size of 200 mesh.

[0136] (6) The granulated powder is directly pressed into a magnetic ring and then pressed into a green body with copper wire.

[0137] (7) The green body is heat treated at 300°C in nitrogen and kept warm for 2 h to obtain a soft magnetic composite material.

[0138] It can be seen from the above preparation method that the soft magnetic composite material provided in this embodiment is composed of amorphous nanocrystalline coated powder and iron-based alloy coated powder. Among them, the amorphous nanocrystalline coated powder includes an amorphous nanocrystalline core and a first insulating coating layer group, and the iron-based alloy coated powder includes a carbonyl iron core and a second insulating coating layer group; the first insulating coating layer group includes a first phosphating layer, a first silicon oxide layer and a first sodium silicate layer stacked, and the first phosphating layer is arranged on the surface of the amorphous nanocrystalline core; the second insulating coating layer group includes a second phosphating layer, a second silicon oxide layer and a second sodium silicate layer stacked, and the second phosphating layer is arranged on the surface of the iron-based core.

[0139] The X-ray diffraction pattern of the amorphous nanocrystalline powder obtained in this example is similar to that of Example 1, so it will not be repeated here. Through calculation and analysis, the crystallinity of the amorphous nanocrystalline powder is 89%, and the average grain size of the nanocrystalline is 17.1 nm.

[0140] After testing, in the amorphous nanocrystalline coated powder obtained in this embodiment, the average thickness of the first phosphide layer is 7nm, the average thickness of the first silicon oxide layer is 13nm, and the average thickness of the first sodium silicate layer is 93nm; in the iron-based alloy coated powder obtained in this embodiment, the average thickness of the second phosphide layer is 53nm, the average thickness of the second silicon oxide layer is 13nm, and the average thickness of the second sodium silicate layer is 38nm.

[0141] Example 3

[0142] This embodiment provides a soft magnetic composite material and a preparation method thereof, the preparation method comprising the following steps:

[0143] (1) Amorphous alloy powder is prepared by water vapor combined atomization method, and its chemical formula is: Fe 65 Co 12 Si8B4Cu 0.8 Nb 2.2 P6V2, after sieving, a powder with a D50 particle size of 20 μm was obtained; the temperature was raised to 550°C at a rate of 250°C / min and kept at this temperature for 2 min to obtain amorphous nanocrystalline powder.

[0144] (2) performing insulation coating treatment on the amorphous nanocrystalline powder, specifically comprising:

[0145] (2.1) Weigh 0.5 parts of phosphoric acid, 0.25 parts of zinc dihydrogen phosphate and 0.25 parts of nickel nitrate, dissolve them in 6 parts of acetone to obtain phosphating solution A; weigh 100 parts of amorphous nanocrystalline powder, add them to the phosphating solution A, stir them evenly at 80° C., control the stirring speed to 120 rpm, until the powder is completely dry, to obtain a first powder A;

[0146] (2.2) Adding silica sol A prepared by mixing 2 parts of silica particles and 20 parts of deionized water to 100 parts of the first powder A, stirring the mixture at 120° C. and controlling the stirring speed to 120 rpm until the powder is completely dry, thereby obtaining a second powder A;

[0147] (2.3) Add sodium silicate solution A prepared by mixing 0.5 parts of sodium silicate nonahydrate and 20 parts of deionized water to 100 parts of the second powder A, stir evenly at 120° C., and control the stirring speed to 120 rpm until the powder is completely dry. After sieving, an amorphous nanocrystalline coated powder with an average particle size of 60 mesh is obtained.

[0148] (3) Insulating and coating the iron-silicon-chromium powder, specifically comprising:

[0149] (3.1) Weigh 0.03 parts of phosphoric acid, 0.01 parts of zinc dihydrogen phosphate and 0.01 parts of nickel nitrate, dissolve them in 6 parts of acetone to obtain phosphating solution B; weigh 100 parts of iron silicon chromium powder with a D50 particle size of 10 μm, add it to the phosphating solution B, stir evenly at 80° C., control the stirring speed to 120 rpm, until the powder is completely dry, to obtain a first powder B;

[0150] (3.2) Adding silica sol B prepared by mixing 2 parts of silica particles and 20 parts of deionized water to 100 parts of the first powder B, stirring the mixture evenly at 120° C. and controlling the stirring speed to 120 rpm until the powder is completely dry, thereby obtaining a second powder B;

[0151] (3.3) Add sodium silicate solution B prepared by mixing 0.5 parts of sodium silicate nonahydrate and 20 parts of deionized water to 100 parts of the second powder B, stir evenly at 120° C. and control the stirring speed to 120 rpm until the powder is completely dry. After sieving, an iron-based alloy coated powder with an average particle size of 60 mesh is obtained.

[0152] (4) Weigh 50 parts of amorphous nanocrystalline coated powder and 50 parts of iron-based alloy coated powder, mix them evenly to obtain graded powder.

[0153] (5) Weigh 1.5 parts of epoxy resin and 20 parts of xylene, mix well, add graded powder, stir thoroughly and air-dry, and sieve to obtain granulated powder with an average particle size of 200 mesh.

[0154] (6) The granulated powder is directly pressed into a magnetic ring and then pressed into a green body with copper wire.

[0155] (7) The green body is heat treated at 100°C in argon and kept warm for 6 hours to obtain a soft magnetic composite material.

[0156] It can be seen from the above preparation method that the soft magnetic composite material provided in this embodiment is composed of amorphous nanocrystalline coated powder and iron-based alloy coated powder. Among them, the amorphous nanocrystalline coated powder includes an amorphous nanocrystalline core and a first insulating coating layer group, and the iron-based alloy coated powder includes a carbonyl iron core and a second insulating coating layer group; the first insulating coating layer group includes a first phosphating layer, a first silicon oxide layer and a first sodium silicate layer stacked, and the first phosphating layer is arranged on the surface of the amorphous nanocrystalline core; the second insulating coating layer group includes a second phosphating layer, a second silicon oxide layer and a second sodium silicate layer stacked, and the second phosphating layer is arranged on the surface of the iron-based core.

[0157] The X-ray diffraction pattern of the amorphous nanocrystalline powder obtained in this example is similar to that of Example 1, so it will not be repeated here. Through calculation and analysis, the crystallinity of the amorphous nanocrystalline powder is 78%, and the average grain size of the nanocrystalline is 13.2 nm.

[0158] After testing, in the amorphous nanocrystalline coated powder obtained in this embodiment, the average thickness of the first phosphide layer is 56nm, the average thickness of the first silicon oxide layer is 68nm, and the average thickness of the first sodium silicate layer is 15nm; in the iron-based alloy coated powder obtained in this embodiment, the average thickness of the second phosphide layer is 7nm, the average thickness of the second silicon oxide layer is 66nm, and the average thickness of the second sodium silicate layer is 14nm.

[0159] Example 4

[0160] This embodiment provides a soft magnetic composite material and a preparation method thereof. In addition to controlling the raw material ratio of the water vapor combined atomization method, the composition of the amorphous alloy powder in step (1) is changed to: Fe 68.5 Co5Si 10 B 12 Cu1Nb 1.2 P2V 0.3 The remaining steps and conditions are the same as those in Example 1, so they will not be described here.

[0161] Example 5

[0162] This embodiment provides a soft magnetic composite material and a preparation method thereof. In addition to controlling the raw material ratio of the water vapor combined atomization method, the composition of the amorphous alloy powder in step (1) is changed to: Fe 77.5 Co2Si9B4Cu1Nb 1.2 P3V 2.3 The remaining steps and conditions are the same as those in Example 1, so they will not be described here.

[0163] Example 6

[0164] This embodiment provides a soft magnetic composite material and a preparation method thereof. Except that the heating rate in step (1) is changed to 100° C. / min, the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.

[0165] Example 7

[0166] This embodiment provides a soft magnetic composite material and a preparation method thereof. Except that the target temperature in step (1) is changed to 400° C., the remaining steps and conditions are the same as those in Example 1 and are not described in detail here.

[0167] Comparative Example 1

[0168] This comparative example provides a soft magnetic composite material and a preparation method thereof, except that in step (1), the amorphous alloy powder is not subjected to rapid heat treatment, that is, amorphous nanocrystalline powder is not obtained, but the amorphous alloy powder is directly subjected to insulation coating treatment. The remaining steps and conditions are the same as those in Example 1 and are not described here.

[0169] Comparative Example 2

[0170] This comparative example provides a soft magnetic composite material and a preparation method thereof, except that step (2.1) is not performed, that is, the amorphous nanocrystalline powder is not subjected to phosphating treatment, but only silica sol coating treatment and sodium silicate coating treatment are performed, and the remaining steps and conditions are the same as those in Example 1, so they are not repeated here.

[0171] Comparative Example 3

[0172] This comparative example provides a soft magnetic composite material and a preparation method thereof, except that step (2.2) is not performed, that is, the amorphous nanocrystalline powder is not subjected to silica sol coating treatment, but only phosphating treatment and sodium silicate coating treatment are performed, and the remaining steps and conditions are the same as those in Example 1, so they are not repeated here.

[0173] Comparative Example 4

[0174] This comparative example provides a soft magnetic composite material and a preparation method thereof, except that step (2.3) is not performed, that is, the amorphous nanocrystalline powder is not subjected to sodium silicate coating treatment, but only phosphating treatment and silica sol coating treatment are performed, and the remaining steps and conditions are the same as those in Example 1, so they are not repeated here.

[0175] Comparative Example 5

[0176] This comparative example provides a soft magnetic composite material and a preparation method thereof, except that step (2) is not performed, that is, the amorphous nanocrystalline powder is not subjected to insulation coating treatment, but the amorphous nanocrystalline powder and the iron-based alloy coated powder are directly mixed to obtain the graded powder. The remaining steps and conditions are the same as those in Example 1 and are not described here.

[0177] Comparative Example 6

[0178] This comparative example provides a soft magnetic composite material and a preparation method thereof, except that step (3) is not performed, that is, the carbonyl iron powder is not subjected to an insulation coating treatment, but the amorphous nanocrystalline coated powder and the carbonyl iron powder are directly mixed to obtain a graded powder. The remaining steps and conditions are the same as those in Example 1 and are not described here.

[0179] Comparative Example 7

[0180] This comparative example provides a soft magnetic composite material and a preparation method thereof. Except that step (2) and step (3) are not performed, that is, directly mixing amorphous nanocrystalline powder and carbonyl iron powder to obtain graded powder, the remaining steps and conditions are the same as those in Example 1, so they are not repeated here.

[0181] Performance Testing

[0182] (1) Inductance: Tested with LCR meter;

[0183] (2) Power consumption: The BH analyzer SY-8218 is used to test the power consumption of the material. The power consumption is obtained by testing the magnetic ring made of the soft magnetic composite material used in the inductor under the same pressing and heat treatment conditions. The dimensions of the magnetic ring are: outer diameter 8 mm, inner diameter 5 mm, thickness 2 mm.

[0184] (3) Salt spray resistance: At any point in the working space, the horizontal collection area is 80 cm 2 The collector collects 1.0-2.0 mL every hour; the salt solution is 5±1wt% sodium chloride solution, and its pH value is 6.5-7.2 when the temperature is 35±2℃. The test temperature is 35±2℃, the test time is 48h, and photos are taken and recorded at 0, 12, 24, 36, and 48h of the test.

[0185] The corresponding test results of the soft magnetic composite materials obtained in Examples 1-7 and Comparative Examples 1-7 are shown in Table 1 below.

[0186] Table 1

[0187]

[0188]

[0189] Figure 2 This is a comparison chart of the soft magnetic composite materials obtained in Example 1 and Comparative Example 7 after 24h salt spray resistance test.

[0190] It can be seen that the present invention realizes mutual insulation between powder particles by sequentially coating the surface of alloy powder in the soft magnetic composite material with a high resistivity phosphide layer, a silicon oxide layer and a sodium silicate layer, effectively reducing the eddy current generated between particles at high frequencies, thereby reducing eddy current losses, improving the overall performance of power devices, and facilitating large-scale promotion and application.

[0191] In addition, the present invention performs rapid heat treatment on the amorphous alloy powder, so that the atoms or molecules in the material obtain sufficient energy to rearrange the structure in a short time. Since the growth process of the grains is significantly suppressed and more crystal nuclei are formed inside the material, the final grain size is nanometer scale, that is, nanocrystals are precipitated to obtain amorphous nanocrystalline powder, which further reduces the coercive force and power consumption of the soft magnetic composite material.

[0192] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A soft magnetic composite material, characterized in that: The soft magnetic composite material is composed of amorphous nanocrystalline coated powder and iron-based alloy coated powder; Wherein, the amorphous nanocrystalline coated powder comprises an amorphous nanocrystalline core and a first insulating coating layer group, and the iron-based alloy coated powder comprises an iron-based core and a second insulating coating layer group; The first insulating coating layer group includes a first phosphide layer, a first silicon oxide layer and a first sodium silicate layer which are stacked, and the first phosphide layer is arranged on the surface of the amorphous nanocrystalline core; The second insulating coating layer group includes a second phosphide layer, a second silicon oxide layer and a second sodium silicate layer which are stacked, and the second phosphide layer is arranged on the surface of the iron-based core.

2. The soft magnetic composite material according to claim 1, characterized in that: The chemical formula of the amorphous nanocrystalline core is: Fe (100-a-b-c-d-e-f-g) Co a Si b B c Cu d Nb e P f V g ; Among them, 5≤a≤12, 3≤b≤12, 4≤c≤10, 0.5≤d≤1.6, 2.0≤e≤3.7, 3≤f≤6, 0.3≤g≤2.0, and 18≤(b+c+f)≤26.

3. The soft magnetic composite material according to claim 1 or 2, characterized in that: In the amorphous nanocrystalline core, the average grain size of the nanocrystalline is 10-20nm and the crystallinity is ≥50%; and / or, the D50 particle size of the amorphous nanocrystalline core is 10-30 μm; And / or, the material of the iron-based core includes any one of carbonyl iron, reduced iron, iron silicon or iron silicon chromium, or a combination of at least two thereof; And / or, the D50 particle size of the iron-based inner core is 4-10 μm.

4. The soft magnetic composite material according to claim 1, characterized in that: The average thickness of the first phosphating layer is 5-70 nm; And / or, the average thickness of the first silicon oxide layer is 10-100 nm; And / or, the average thickness of the first sodium silicate layer is 10-100 nm; And / or, the average thickness of the second phosphide layer is 5-70 nm; And / or, the average thickness of the second silicon oxide layer is 10-100 nm; And / or, the average thickness of the second sodium silicate layer is 10-100 nm.

5. A method for preparing the soft magnetic composite material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) Amorphous alloy powder is prepared by a water vapor combined atomization method, and amorphous nanocrystalline powder is obtained after rapid heat treatment; (2) subjecting the amorphous nanocrystalline powder and the iron-based alloy powder to phosphating treatment, silica sol coating treatment and sodium silicate coating treatment respectively, to obtain amorphous nanocrystalline coated powder and iron-based alloy coated powder respectively; (3) mixing amorphous nanocrystalline coated powder and iron-based alloy coated powder to obtain graded powder; (4) The graded powder is sequentially granulated, pressed and heat treated to obtain a soft magnetic composite material.

6. The preparation method according to claim 5, characterized in that: The heating rate of the rapid heat treatment in step (1) is 200-250°C / min, and the target temperature is 450-600°C.

7. The preparation method according to claim 5 or 6, characterized in that: The phosphating treatment in step (2) comprises: mixing the alloy powder and the phosphating solution, stirring them uniformly under heating conditions, and drying them to obtain a first powder; Wherein, the alloy powder includes amorphous nanocrystalline powder and / or iron-based alloy powder; and / or, the solute of the phosphating solution includes phosphoric acid, zinc dihydrogen phosphate and nickel nitrate; And / or, the mixing mass ratio of the solute of the phosphating solution to the alloy powder is (0.05-1):100; And / or, the solvent of the phosphating solution includes any one of deionized water, anhydrous ethanol or acetone, or a combination of at least two thereof; And / or, the mixing mass ratio of the solvent of the phosphating solution to the alloy powder is (6-20):

100.

8. The preparation method according to claim 7, characterized in that: The silica sol coating treatment in step (2) comprises: mixing the first powder and the silica sol, stirring them evenly under heating conditions, and drying them to obtain a second powder; Wherein, the silica sol is a dispersion of silica particles in deionized water, and the mass ratio of the silica particles to the deionized water is (2.5-30):100; And / or, the mixing mass ratio of the silicon dioxide particles to the first powder in the silica sol is (0.5-3):

100.

9. The preparation method according to claim 8, characterized in that: The sodium silicate coating treatment in step (2) comprises: mixing the second powder and the sodium silicate solution, stirring evenly under heating conditions, and drying to obtain an amorphous nanocrystalline coated powder and / or an iron-based alloy coated powder; Wherein, the sodium silicate solution is a mixed solution of sodium silicate nonahydrate and deionized water, and the mass ratio of the sodium silicate nonahydrate to the deionized water is (2.5-20):100; And / or, the mixing mass ratio of sodium silicate nonahydrate to the second powder in the sodium silicate solution is (0.5-2):

100.

10. The preparation method according to claim 5, characterized in that: The mixing mass ratio of the amorphous nanocrystalline coated powder and the iron-based alloy coated powder in step (3) is (25-100):100; And / or, the granulation in step (4) comprises: mixing the graded powder and the epoxy resin solution, and drying to obtain granulated powder; Wherein, the solvent of the epoxy resin solution includes any one of acetone, ethanol, toluene or xylene, or a combination of at least two thereof; And / or, the heat treatment in step (4) is carried out in air, nitrogen or argon.

Citation Information

Cited By

  • Metal soft magnetic composite material, preparation method thereof and magnetic device

    CN121545869A

  • Metallic soft magnetic composite material, method for producing the same, and magnetic device

    CN121545869B